The Students’ Perception on YouTube as Online Learning Media for Indonesian Language General Course During Covid 19 Pandemic - Siti Mutmainah; Ora Gorez Uke; Dian Triana; Erisy Syawiril Ammah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Covid 19 pandemic has had huge effect in both health industry and education industry. This phenomenon requires teachers or lecturers to use online learning media as an alternative to fulfill students’ cognitive, affective, and social skill. YouTube is one of many online learning alternatives available. The purpose of this research is to describe the utilization of YouTube as an online learning media during COVID-19. This research was conducted particularly to Indonesian language general course in Jember University. Based on the result, the students perceive prefer and do not prefer on YouTube as learning media. This research method uses cross-section design, applied to 118 respondents in various college classes and various majors with main focus on Indonesian language general course in Jember University. The result of this research shows the YouTube’s features as a tool to teach such as: customized thumbnail, playlist, share link, and end screens. There are two phases for lecturers to utilize YouTube as online learning media. The first phase is preparation and the second phase is implementation. Based on the research, 90% students perceive that YouTube is effective and preferable media, whilst the rest of 10% perceive do not prefer toward YouTube as the media chosen.